Effects of understanding wellbeing on psychological aspects and wound healing in patients with diabetic foot ulcer recurrence: a pilot randomised controlled trial. (2018) - Arisandi, Defa; Haryanto, Haryanto; Jais, Suriadi; Oe, Makoto; Okuwa, Mayumi; Nakatani, Toshio; Sanada, Hiromi; Sugama, Junko
No abstract available